Athrogenic Indices Can Predict Atherosclerosis in Patients with Sarcoidosis: Sarcoidosis and Atherosclerosis - Selendili, Okan; Günay, Ersin; Kacar, Emre; Cilekar, Sule; Oz, Gurhan; Dumanli, Ahmet; Günay, Sibel (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background: Sarcoidosis is a multisystemic disease of unknown etiology characterized by non-caseating granulomatous inflammation. In this study, we aimed to investigate the efficiency of atherogenic indices and ultrasonographic evaluation of carotid artery on predictive value of diagnosis of atherosclerosis in patients with sarcoidosis. Methods: We included 44 subjects which were followed with diagnosis of sarcoidosis and 53 healthy subjects–for control group- matched with age and gender. Laboratory findings, pulmonary function tests and carotis artery ultrasonography data of all participants were evaluated. Results: Of all patients with sarcoidosis 70.5% was female and mean age was 35.36±7.18 years. 64.2% of the control patients were female and the mean age was 33.58±8.13 years (P=0.511 and P=0.191, respectively). High-density-lipoprotein cholesterol level in the sarcoidosis group was significantly lower than the control patients (P=0.017), while other cholesterol levels were higher than the control patients (P<0.05). Intima-media thickness and peak systolic velocity (PSV) of carotid artery were higher in patients with sarcoidosis (P<0.001 and P=0.009, respectively). Atherogenic indices (Atherogenic Index (AI), Atherogenic Coefficient (AC) and Cardiogenic Risk Ratio (CRR)) were calculated much greater in patients with sarcoidosis than control (P<0.001, for all parameters). There was a positive correlation between Intima-Media thickness and PSV, AI, AC, and CRR. A positive correlation between PSV and atherogenic indices was also detected. Conclusions: Sarcoidosis is a predisposing cause for atherosclerosis. Atherogenic indices, intima-media thickness of carotid artery and PSV could be considered as a useful predictor for atherosclerosis and cardiovascular diseases in asymptomatic sarcoidosis patients.